Combining interictal intracranial EEG and fMRI to compute a dynamic resting-state index for surgical outcome validation - Boerwinkle, Varina L.; Gunnarsdottir, Kristin M.; Sussman, Bethany L.; Wyckoff, Sarah N.; Cediel, Emilio G.; Robinson, Belfin; Reuther, William R.; Kodali, Aryan; Sarma, Sridevi V. (Frontiers in Network Physiology, 2025)
IntroductionAccurate localization of the seizure onset zone (SOZ) is critical for successful epilepsy surgery but remains challenging with current techniques. We developed a novel seizure onset network characterization tool that combines dynamic biomarkers of resting-state intracranial stereoelectroencephalography (rs-iEEG) and resting-state functional magnetic resonance imaging (rs-fMRI), vetted against surgical outcomes. This approach aims to reduce reliance on capturing seizures during invasive monitoring to pinpoint the SOZ.MethodsWe computed the source-sink index (SSI) from rs-iEEG for all implanted regions and from rs-fMRI for regions identified as potential SOZs by noninvasive modalities. The SSI scores were evaluated in 17 pediatric drug-resistant epilepsy (DRE) patients (ages 3–15 years) by comparing outcomes classified as successful (Engel I or II) versus unsuccessful (Engel III or IV) at 1 year post-surgery.ResultsOf 30 reviewed patients, 17 met the inclusion criteria. The combined dynamic index (im-DNM) integrating rs-iEEG and rs-fMRI significantly differentiated good (Engel I–II) from poor (Engel III–IV) surgical outcomes, outperforming the predictive accuracy of individual biomarkers from either modality alone.ConclusionThe combined dynamic network model demonstrated superior predictive performance than standalone rs-fMRI or rs-iEEG indices.SignificanceBy leveraging interictal data from two complementary modalities, this combined approach has the potential to improve epilepsy surgical outcomes, increase surgical candidacy, and reduce the duration of invasive monitoring.